Development and first evaluation of a novel preventive knee brace for alpine ski racing - Spitzenpfeil, P.; Olvermann, M.; Grabisch, A.; Diez, L.; Junior, V.; Huber, A.; Waibel, K.; Moritz, E.; Stehling, G.; Valtingoier, I.; Semsch, H.; Nusser, M.; et al. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
In a process of more than 4 years, our interdisciplinary research group developed a novel preventive knee brace in conjunction with a specialized compression underwear. Our first preventive brace models have been already introduced into the Alpine World Cup racing scenery. In this article, the developmental process, basic laboratory research, and first in vivo evaluations including exemplary results were presented.